KINERJA DINAS PEKERJAAN UMUM DALAM PENGELOLAAN JALAN KABUPATEN ENREKANG - Mahyuddin, Mahyuddin; Ansari, Muhammad Isa; Parawangi, Anwar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The purpose of this study was to determine the performance of the public works department in managing roads in Enrekang district. This type of research is descriptive qualitative research, data collection techniques are observation, interviews and documentation. The results of this research are the performance of the public works department in managing roads in Enrekang district using by using indicators of responsiveness regarding performance capabilities and how to maintain the performance capabilities of the public works department in the management of enrekang district roads it has shown very good performance results where workers always try their best to maximize their work even though the working conditions are so tough then the workers are always patient and motivating themselves that about the duties and responsibilities that must be carried out even with any conditions